2010
DOI: 10.1259/dmfr/69910245
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between computed tomography and clinical evaluation in tumour/node stage and follow-up of oral cavity and oropharyngeal cancer

Abstract: Objectives:The aim was to verify the concordance of CT evaluation among four radiologists (two oral and maxillofacial and two medical radiologists) at the TN (tumour/node) stage and in the follow-up of oral cavity and oropharyngeal cancer patients. The study also compared differences between clinical and CT examinations in determining the TN stage. Methods:The following clinical and tomographic findings of 15 non-treated oral cavity and oropharyngeal cancer patients were compared: tumour size, bone invasion an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Among these results, three cases were staged as belonging to the IVA grouping, which represents lesions which are larger and at a more advanced stage, thereby facilitating diagnosis. 15 This confirms the greater importance of the MRI examination for smaller lesions. The definition of grouping by stages is critical in determining the patient's treatment plan, prognosis and survival span.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Among these results, three cases were staged as belonging to the IVA grouping, which represents lesions which are larger and at a more advanced stage, thereby facilitating diagnosis. 15 This confirms the greater importance of the MRI examination for smaller lesions. The definition of grouping by stages is critical in determining the patient's treatment plan, prognosis and survival span.…”
Section: Discussionsupporting
confidence: 54%
“…Calibration of the observers may have been decisive in achieving the agreement levels and should be used in joint training programs that prepare medical and oral radiologists to diagnose oral cancer at reference centers providing multidisciplinary care. 15 There was substantial and significant agreement between the clinical and MRI staging performed by Observers 2 and 4 for N stage. Nevertheless, case number 3, clinically staged as N1, was staged as N0 by two observers (1 and 3) in the MRI examination.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The OMRs also identified a greater number of metastatic lymph nodes on CECT compared with the MRs. A previous study has demonstrated that there were differences between different radiologists in determining the N-stage by CECT, but with significant agreement for the T-stage. 25 Regarding the medical radiologists, a lower agreement was observed between them. This could be explained by the fact that they are general radiologists because in Brazil head and neck radiology is not usually a subspecialty.…”
Section: Discussionmentioning
confidence: 97%
“…The rating of possible lymph node metastases is often difficult because of the subjective observerbased cut-off size of suspicious lymph nodes. A size of 10 mm in diameter is often regarded as a borderline morphological cut-off size for positive metastases or for the rating of necrotic tissue areas inside a lymph node (Figueiredo et al, 2010). As CT diagnosis is based purely on morphology, small metastatic lymph nodes and uneventful local tumour recurrence can be overlooked or misinterpreted because of postoperative anatomical changes or distortion, as mentioned above.…”
Section: Ctmentioning
confidence: 99%